2011
DOI: 10.1016/j.jalz.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Costs of care in a mild‐to‐moderate Alzheimer clinical trial sample: Key resources and their determinants

Abstract: Informal care is the most important component of costs of care in a mild-to-moderate Alzheimer clinical trial sample, and it is primarily driven by the ADL-ability of the patient. Investigators should focus on the assessment of this economic endpoint because a significant treatment effect on this resource is likely to also affect total costs of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 64 publications
7
59
1
1
Order By: Relevance
“…The cost of delivering the intervention will be calculated using time logs retained by interventionists of treatment and attention control groups that includetime spent in preparation and provision of respective interventions, and supervision and training and materials used. Healthcare utilization will be captured using the Resource Utilization in Dementia—Lite (RUD-Lite) (Gustavsson et al, 2010; Gustavsson et al, 2011; Neubauer et al, 2009; Wimo et al, 1998; Wimo et al, 2007; Wimo et al, 2010; Wimo et al, 2013) and the Service Use and Resource Form (SURF) (Rosenheck et al, 2006; Rosenheck et al, 2007; Schneider et al, 2001), questionnaires developed specifically for clinical trials involving persons with dementia. Utilization will be converted to cost by applying prevailing reimbursement rates and case mix-based costs (using DRGs) for inpatient stays.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of delivering the intervention will be calculated using time logs retained by interventionists of treatment and attention control groups that includetime spent in preparation and provision of respective interventions, and supervision and training and materials used. Healthcare utilization will be captured using the Resource Utilization in Dementia—Lite (RUD-Lite) (Gustavsson et al, 2010; Gustavsson et al, 2011; Neubauer et al, 2009; Wimo et al, 1998; Wimo et al, 2007; Wimo et al, 2010; Wimo et al, 2013) and the Service Use and Resource Form (SURF) (Rosenheck et al, 2006; Rosenheck et al, 2007; Schneider et al, 2001), questionnaires developed specifically for clinical trials involving persons with dementia. Utilization will be converted to cost by applying prevailing reimbursement rates and case mix-based costs (using DRGs) for inpatient stays.…”
Section: Discussionmentioning
confidence: 99%
“…In this questionnaire, caregiver time is evaluated by asking how much time is spent on activities of daily living (ADL), instrumental ADL, and supervision on an average caregiving day in the past 30 days. According to common practice [22], the total reported time was capped at maximum 18 h per day to avoid overestimation [23]. …”
Section: Design and Methodsmentioning
confidence: 99%
“…A total of 47 studies reported economic data on the direct and indirect costs of AD for the seven selected countries; the remaining five studies reported aggregated international data [50][51][52][53][54]. Among the 47 studies, 17 primary source articles were identified in which cost component data were available and presented according to AD severity or patients' living conditions; two for France [55,56], four for Germany [7,[57][58][59], zero for Italy, three for the Netherlands [8,51,60], four for Spain [49,[61][62][63], two for the UK [64,65], and two for the USA [9,66].…”
Section: Economic (Direct and Indirect Costs)mentioning
confidence: 99%